Drug smuggler nation : Narcotics and the Netherlands, 1920-1995 - Snelders, Stephen (Book collections on Project MUSE., 2021)
Drug smuggler nation shows how and why the Netherlands developed in the course of the twentieth century into a central hub of the international illegal drug trade, and develops a model of a 'criminal anarchy' that is historically, socially, and culturally embedded in Dutch society, in both native and migrant communities, to explain the failures of the state's regulatory policies and law enforcement.